The novel bio-SYNTAX scoring system for predicting the prognosis of patients undergoing percutaneous coronary intervention with left main coronary artery disease - Yoon, Jae Yong; Lee, Jang Hoon; Kim, Hong Nyun; Kim, Namkyun; Jang, Se Yong; Bae, Myung Hwan; Yang, Dong Heon; Park, Hun Sik; Cho, Yongkeun (Frontiers in Cardiovascular Medicine, 2022)
Background: There has been few simple and effective risk model incorporating biomarkers in patients with left main coronary artery (LMCA) stenosis. Methods: Patients who underwent percutaneous coronary intervention (PCI) for LMCA stenosis with drug-eluting stent (n=275) were analyzed in this study. We have developed the Bio-Clinical SYNTAX score (Bio-CSS) incorporating N-terminal pro-B type natriuretic peptide (NT-proBNP) and validated whether Bio-CSS would improve the ability to predict major adverse cardiac events (MACEs) compared with SYNTAX score (SS) and SS II. The MACEs were defined as death, non-fatal myocardial infarction, and repeat revascularizations. Results: Bio-CSS (34.7±18.3 versus 51.9±28.4, p<0.001) as well as SS (23.6±7.3 versus 26.7±8.1, p=0.003) and SS II (29.4±9.9 versus 36.1±12.8, p<0.001) was significantly higher in patients with MACEs. In Cox-proportional hazards model, log Bio-CSS (HR 8.31, 95% CI 1.84 – 37.55) was an independent prognostic factor for MACEs after adjustment for confounding variables. In receiver operating characteristics curves, area under the curve of Bio-CSS was significantly higher compared with those of SS (0.608 versus 0.706, p =0.001) and SS II (0.655 versus 0.706, p =0.026). Patients were categorized into 3 groups according to tertiles of Bio-CSS. Patients in the highest tertile of Bio-CSS had significantly higher MACEs compared with the lower 2 tertiles (log-rank p < 0.001). Conclusions: In patients who underwent PCI for LMCA stenosis, novel Bio-CSS improve the discrimination accuracy of established combined score such as SS and SS II. Bio-CSS adding NT-proBNP to clinical and angiographic findings could provide useful long-term prognostic information in these patients.